2001
DOI: 10.1590/s0101-81752001000200014
|View full text |Cite
|
Sign up to set email alerts
|

Culicideofauna (Diptera) encontrada em entrenós de taquara de uma mata residual na área urbana de Londrina, Paraná, Brasil

Abstract: ABSTRACT. Fauna ofCulicidae (Diptera) found in the internodes ofthe bamboo in a residual forest in the urban area ofLondrina -Paraná, Brazil. A fragment of a forest, located in the urban area ofLondrina, Paraná, Brazil,was chosen to represent the area torthis study. Many Meroslachys Spreng, 1824 bamboo, which were naturally pertorated and, therefore, ready to retain water, were found in the interior ofthis forest. Bamboo were collected every fifteen days during lield actions. They were lhen measured and cutmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
0
12
0
4
Order By: Relevance
“…De acordo com o hábito das espécies, estas podem depositar seus ovos, em ocos de árvores (JENKINS & CARPENTER 1946), SOTA et al 1994); nas axilas de plantas, em conchas de moluscos (FORATTINI 2002), em bromélias (FORATTINI & MARQUES 2000), em entrenós de bambu e taquara (SOTA & MOGI 1996, LOZOVEI 1998, ZEQUI & LOPES 2001, nas nascentes de água ou nos ribeirões existentes em seu interior (CONSOLIM et al 1993, LOPES & LOZOVEI 1995, QUINTERO et al 1996, LOPES et al 2002.…”
unclassified
“…De acordo com o hábito das espécies, estas podem depositar seus ovos, em ocos de árvores (JENKINS & CARPENTER 1946), SOTA et al 1994); nas axilas de plantas, em conchas de moluscos (FORATTINI 2002), em bromélias (FORATTINI & MARQUES 2000), em entrenós de bambu e taquara (SOTA & MOGI 1996, LOZOVEI 1998, ZEQUI & LOPES 2001, nas nascentes de água ou nos ribeirões existentes em seu interior (CONSOLIM et al 1993, LOPES & LOZOVEI 1995, QUINTERO et al 1996, LOPES et al 2002.…”
unclassified
“…(Diptera, Culicidae) from artificially perforated bamboo in the rain forest of southern Brazil (Lozovei 1998), mixed ombrophylous forest (Marcondes et al 2006) and seasonal semideciduous forest (Zequi & Lopes 2001). However, the biology of its immature forms is poorly known.…”
Section: Developmental Time Of Immature Forms Of Sabethes Aurescens Lutzmentioning
confidence: 99%
“…This author recorded 17 species of mosquitoes, most of them of the Sabethini tribe, and highlighted the specialization of the females to localize the breeding sites. Martins Da Silva et al (2004) reported three culicids, two native species and the invasive Aedes (Stegomyia) albopictus (Skuse), from stumps of bamboo in the Brazilian Atlantic Forest, and Zequi and Lopes (2001), reported 10 mosquito species inhabiting Merostachys bamboo, in a bush in the urban area of Londrina, Brazil, where Sabethini were dominant. In Colombia, Barajas et al (2013) reported nine mosquito species breeding in internodes and stumps of Guadua angustifolia Kunth.…”
Section: Introductionmentioning
confidence: 99%